So you think you can write? : the definitive guide to successful online writing - Mccoy, Julia, ....- (S.l. : CreateSpace Independent Publishing Platform, 2016)
In So You Think You Can Write?, you'll learn every skill it takes to write great copy for the web, from the absolute fundamentals of using storytelling in great online content all the way to knowing how to write for both search engines and people, what it takes to craft different forms of content on the web, and much more; plus, there's a bonus chapter revealing how to market yourself and make income as an online copywriter in an modern world. Written by Julia McCoy, who spent years of her life teaching herself the elements of successful online writing and launched a writing business that hit seven figures within five years, this book is your essential blueprint to learning what it takes to write great online copy, both as a freelancer and brand/business owner.